IJCM_378A: Introduction of Elective modules Block 2 in undergraduate new Competency based Medical Education (CBME) Curriculum: Perception of students - Sharma Mini; Verma Nirmal; Das Durga (Wolters Kluwer Medknow Publications, 2024)
Background: The new competency based medical education curriculum (CBME) introduced 2 months electives (2 blocks of 4 weeks) in the curriculum for undergraduates medical students during their study periods (at the completion of phase 3 part 1). Elective is an optional course, generally of short duration, where students can opt 'electives' as per their topic of interest, career preference and availability at institutes. During electives students get an opportunity to differentiate during medical training, experience applicative use of knowledge and develop applied skills under the supervision and guidance of preceptors. Objective: To assess the Students perception regarding Elective modules (Block-2) necessity and benefit. Methodology: This was a cross sectional study conducted in Department of Community Medicine, Pt JNM Medical college, Raipur and Associated tertiary care hospital Dr. BRAM hospital. Raipur, Chhattisgarh in which 181 undergraduates medical students were interviewed through online mode using google form and was circulated to all via WhatsApp group. Results: Total 181 study subjects were participated in which 56.4% male and 43.6% female. Sixty-eight percent study subjects agreed that elective posting increases their knowledge and skill. Most of the students 66(36.5%) perceived elective posting very good Conclusion: This study concluded that students had very good overall experience of elective posting which proved to be helpful in improving their knowledge, clinical skills and enhanced their learning opportunities.